Molecular structure of trans-[Co(NH₃)₄(NH₂CH₃)Cl](ClO₄)₂ - Benzo, Fabián (1998)
The title compound crystallizes in the orthorhombic space group Pnma, with a = 7.9209(5), b = 9.818(1), c = 16.867(2) Å, and Z = 4. The structure was solved employing 1864 independent x-ray reflections with I>2σ(I) by Patterson and difference Fourier techniques and refined by full-matrix least-squares to R = 0.036. The trans-[Co(NH₃)₄(NH₂CH₃)Cl](ClO₄)₂ molecule is on a crystallographic mirror plane. The cobalt ion is in an elongated octahedral coordination with four equatorial ammonia ligands [average Co–N distance equal to 1.966(2) Å], an axial methylamine [Co–N=1.965(3)Å], and an axial chlorine ion [Co–Cl=2.2771(9)Å]. Kinetic steric effects of the complex are interpreted in terms of structural results.